High-strength diamond saw blade tool bit material

By using alloy cutter head materials of copper, iron, nickel, cobalt, tin, high-purity porcelain powder and diamond materials, combined with solid phase sintering method, the problem of low strength of diamond saw blade cutter heads is solved, and higher compressive strength and service life are achieved.

CN119530632APending Publication Date: 2025-02-28DANYANG YONGFENG HARDWARE ELECTROMECHANICAL EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411545110.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing diamond saw blade tips are not strong and are prone to fall off, resulting in a shorter service life.

Method used

Alloy cutter head materials using copper, iron, nickel, cobalt, tin, high-purity porcelain powder and diamond are prepared by solid phase sintering to improve the strength of the saw blade cutter head.

Benefits of technology

It significantly improves the compressive strength and service life of the saw blade cutting head and enhances the cutting ability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-strength diamond saw blade tool bit material which comprises the following components in parts by weight: 20-38 parts of copper, 40-55 parts of iron, 4-20 parts of nickel, 4-15 parts of cobalt, 4-12 parts of tin, 10-22 parts of high-purity ceramic powder and 2-4 parts of diamond. Wherein the high-purity ceramic powder comprises yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder and magnesium hydroxide powder, and the content ratio of the yttrium oxide powder to the strontium carbonate powder to the zinc oxide powder to the sodium carbonate powder to the magnesium hydroxide powder is 1: 2: 4: 1: 1.5. High-purity ceramic powder is prepared through a solid-phase sintering method and added into alloy tool bit powder, the strength of the saw blade tool bit is improved, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diamond saw blades, and in particular relates to a high-strength diamond saw blade head material. Background Art

[0002] Diamond is the hardest material found in the world and can be used in large quantities in industry, and diamond cutting tools have become an indispensable material for processing various hard materials. Diamond cutting tools are made by mixing metal powder and artificial diamond particles, pressing and sintering. Moreover, with the continuous development of society, the scale of infrastructure construction continues to expand, which also provides a broader application market for diamond tools. Among diamond cutting tools, diamond saw blades have the widest range of use. Diamond saw blades have been widely used in the cutting and processing of marble, granite, concrete, asphalt, ceramics, glass, jewelry, jade, semiconductors and other materials. With the continuous development of technology, the requirements for cutting efficiency and cutting strength are getting higher and higher.

[0003] At present, the diamond saw blade segment is added with strong materials such as W, WC, and W2C, but the wettability with the matrix metal is poor and difficult to sinter, which leads to insufficient holding force of the matrix on W, WC, etc., and easy to fall off during use, greatly shortening the life of the saw blade. At the same time, the amount of wear-resistant phases such as WC and W added in traditional diamond circular saw blades is difficult to exceed 60%, because with the increase of the amount of W, WC, etc. added, the density of the segment sintering decreases, the density of the segment decreases, the hardness and brittleness of the segment increases, and the strength decreases, which is easy to cause serious consequences such as tooth breakage during the cutting process. Therefore, it is necessary to further improve the material of the diamond saw blade segment. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a high-strength diamond saw blade segment material to avoid the trouble of low strength of the previous diamond saw blade segments.

[0005] In order to solve the above technical problems, the present invention discloses a high-strength diamond saw blade segment material, which comprises, by weight: 20-38 parts of copper, 40-55 parts of iron, 4-20 parts of nickel, 4-15 parts of cobalt, 4-12 parts of tin, 10-22 parts of high-purity porcelain powder, and 2-4 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0006] According to one embodiment of the present invention, the above-mentioned parts by weight include: 20 parts of copper, 40 parts of iron, 4 parts of nickel, 4 parts of cobalt, 4 parts of tin, 10 parts of high-purity porcelain powder, and 2 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0007] According to one embodiment of the present invention, the above-mentioned parts by weight include: 38 parts of copper, 55 parts of iron, 20 parts of nickel, 15 parts of cobalt, 12 parts of tin, 22 parts of high-purity porcelain powder, and 4 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0008] According to one embodiment of the present invention, the above-mentioned parts by weight include: 29 parts of copper, 47 parts of iron, 12 parts of nickel, 9 parts of cobalt, 8 parts of tin, 16 parts of high-purity porcelain powder, and 3 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0009] According to one embodiment of the present invention, the high-purity ceramic powder is prepared by a solid phase sintering method.

[0010] Compared with the prior art, the present invention can achieve the following technical effects: High-purity porcelain powder is prepared by solid phase sintering method and added to alloy cutter head powder to improve the strength of saw blade cutter head and extend its service life.

[0011] Of course, any product implementing the present invention does not necessarily need to achieve all of the above-mentioned technical effects at the same time. DETAILED DESCRIPTION

[0012] The following will describe the implementation methods of the present invention in detail with reference to examples, so that the implementation process of how the present invention applies technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0013] The present invention discloses a high-strength diamond saw blade segment material, which comprises, by weight: 20-38 parts of copper, 40-55 parts of iron, 4-20 parts of nickel, 4-15 parts of cobalt, 4-12 parts of tin, 10-22 parts of high-purity porcelain powder, and 2-4 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5. Example 1

[0014] The following powders are provided in parts by weight: 20 parts of copper, 40 parts of iron, 4 parts of nickel, 4 parts of cobalt, 4 parts of tin, 10 parts of high-purity porcelain powder, and 2 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0015] High-purity porcelain powder is prepared by solid-phase sintering appropriate amounts of yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder to form a mixed powder, which is then transferred to a nylon ball mill, added with ball milling media and grinding balls, and placed in a planetary ball mill for wet grinding. After the ball mill slurry is dried, a binder is added, mixed, and sieved; on a one-way press, it is pressed into a blank at a pressure of 100 to 150 MPa, and finally the compact is placed in a box-type resistance furnace for heating and sintering to obtain high-purity porcelain powder. High-purity porcelain powder is mixed with copper, iron, nickel, cobalt, tin, and diamond to form a mixed powder, which is cold pressed after mixing, and then hot pressed and sintered to finally obtain a diamond cutter head.

[0016] Place the diamond segment sample on the clamping device of the strength testing machine and adjust the sample to the correct direction according to the test requirements.

[0017] First, install the bend fixture on the table of the compression testing machine, and then place the sample on the bend fixture.

[0018] After placing it, install the pressure head so that the pressure head lightly touches the blade.

[0019] Start the test: Start the testing machine and let the indenter apply downward pressure to bend and deform the blade until it breaks. During the loading process, the load and displacement data are recorded in real time, and other data such as temperature are recorded as needed.

[0020] Analysis results: After the test, the hardness and compressive strength of the sample were analyzed based on the experimental data. Common results include indicators such as compressive strength and compressive strain. The compressive strength was measured to be 2300MP. Example 2

[0021] The following powders are available in parts by weight: 38 parts of copper, 55 parts of iron, 20 parts of nickel, 15 parts of cobalt, 12 parts of tin, 22 parts of high-purity porcelain powder, and 4 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0022] High-purity porcelain powder is prepared by solid-phase sintering appropriate amounts of yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder to form a mixed powder, which is then transferred to a nylon ball mill, added with ball milling media and grinding balls, and placed in a planetary ball mill for wet grinding. After the ball mill slurry is dried, a binder is added, mixed, and sieved; on a one-way press, it is pressed into a blank at a pressure of 100 to 150 MPa, and finally the compact is placed in a box-type resistance furnace for heating and sintering to obtain high-purity porcelain powder. High-purity porcelain powder is mixed with copper, iron, nickel, cobalt, tin, and diamond to form a mixed powder, which is cold pressed after mixing, and then hot pressed and sintered to finally obtain a diamond cutter head.

[0023] Place the diamond segment sample on the clamping device of the strength testing machine and adjust the sample to the correct direction according to the test requirements.

[0024] First, install the bend fixture on the table of the compression testing machine, and then place the sample on the bend fixture.

[0025] After placing it, install the pressure head so that the pressure head lightly touches the blade.

[0026] Start the test: Start the testing machine and let the indenter apply downward pressure to bend and deform the blade until it breaks. During the loading process, the load and displacement data are recorded in real time, and other data such as temperature are recorded as needed.

[0027] Analysis results: After the test, the hardness and compressive strength of the sample were analyzed based on the experimental data. Common results include indicators such as compressive strength and compressive strain. The compressive strength was measured to be 2600MP. Example 3

[0028] The following powders are available in parts by weight: 29 parts of copper, 47 parts of iron, 12 parts of nickel, 9 parts of cobalt, 8 parts of tin, 16 parts of high-purity porcelain powder, and 3 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.5.

[0029] High-purity porcelain powder is prepared by solid-phase sintering appropriate amounts of yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder to form a mixed powder, which is then transferred to a nylon ball mill, added with ball milling media and grinding balls, and placed in a planetary ball mill for wet grinding. After the ball mill slurry is dried, a binder is added, mixed, and sieved; on a one-way press, it is pressed into a blank at a pressure of 100 to 150 MPa, and finally the compact is placed in a box-type resistance furnace for heating and sintering to obtain high-purity porcelain powder. High-purity porcelain powder is mixed with copper, iron, nickel, cobalt, tin, and diamond to form a mixed powder, which is cold pressed after mixing, and then hot pressed and sintered to finally obtain a diamond cutter head.

[0030] Place the diamond segment sample on the clamping device of the strength testing machine and adjust the sample to the correct direction according to the test requirements.

[0031] First, install the bend fixture on the table of the compression testing machine, and then place the sample on the bend fixture.

[0032] After placing it, install the pressure head so that the pressure head lightly touches the blade.

[0033] Start the test: Start the testing machine and let the indenter apply downward pressure to bend and deform the blade until it breaks. During the loading process, the load and displacement data are recorded in real time, and other data such as temperature are recorded as needed.

[0034] Analysis results: After the test, the hardness and compressive strength of the sample were analyzed based on the experimental data. Common results include indicators such as compressive strength and compressive strain. The compressive strength was measured to be 3200MP. Example 4

[0035] The following powders are available in parts by weight: 29 parts of copper, 47 parts of iron, 12 parts of nickel, 9 parts of cobalt, 8 parts of tin, 16 parts of high-purity porcelain powder, and 3 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:1.5:3:1:2.

[0036] High-purity porcelain powder is prepared by solid-phase sintering appropriate amounts of yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder to form a mixed powder, which is then transferred to a nylon ball mill, added with ball milling media and grinding balls, and placed in a planetary ball mill for wet grinding. After the ball mill slurry is dried, a binder is added, mixed, and sieved; on a one-way press, it is pressed into a blank at a pressure of 100 to 150 MPa, and finally the compact is placed in a box-type resistance furnace for heating and sintering to obtain high-purity porcelain powder. High-purity porcelain powder is mixed with copper, iron, nickel, cobalt, tin, and diamond to form a mixed powder, which is cold pressed after mixing, and then hot pressed and sintered to finally obtain a diamond cutter head.

[0037] Place the diamond segment sample on the clamping device of the strength testing machine and adjust the sample to the correct direction according to the test requirements.

[0038] First, install the bend fixture on the table of the compression testing machine, and then place the sample on the bend fixture.

[0039] After placing it, install the pressure head so that the pressure head lightly touches the blade.

[0040] Start the test: Start the testing machine and let the indenter apply downward pressure to bend and deform the blade until it breaks. During the loading process, the load and displacement data are recorded in real time, and other data such as temperature are recorded as needed.

[0041] Analysis results: After the test, the hardness and compressive strength of the sample are analyzed based on the experimental data. Common results include indicators such as compressive strength and compressive strain. The compressive strength was measured to be 2500MP.

[0042] In summary, the present invention prepares high-purity porcelain powder by solid-phase sintering method, and adds the powder to alloy cutter head to improve the strength of the saw blade cutter head and increase the service life.

[0043] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A high-strength diamond saw blade segment material, characterized in that: Included by weight: 20-38 parts of copper, 40-55 parts of iron, 4-20 parts of nickel, 4-15 parts of cobalt, 4-12 parts of tin, 10-22 parts of high-purity porcelain powder, and 2-4 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.

5.

2. The high-strength diamond saw blade segment material according to claim 1, characterized in that: Included by weight: 20 parts of copper, 40 parts of iron, 4 parts of nickel, 4 parts of cobalt, 4 parts of tin, 10 parts of high-purity porcelain powder, and 2 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.

5.

3. The high-strength diamond saw blade segment material according to claim 1, characterized in that: Included by weight: 38 parts of copper, 55 parts of iron, 20 parts of nickel, 15 parts of cobalt, 12 parts of tin, 22 parts of high-purity porcelain powder, and 4 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.

5.

4. The high-strength diamond saw blade segment material according to claim 1, characterized in that: Included by weight: 29 parts of copper, 47 parts of iron, 12 parts of nickel, 9 parts of cobalt, 8 parts of tin, 16 parts of high-purity porcelain powder, and 3 parts of diamond; wherein the high-purity porcelain powder includes yttrium oxide powder, strontium carbonate powder, zinc oxide powder, sodium carbonate powder, and magnesium hydroxide powder, and the content ratio is 1:2:4:1:1.

5.

5. The high-strength diamond saw blade segment material according to claim 1, characterized in that: The high-purity porcelain powder is prepared by a solid phase sintering method.